EFFICIENCY OF SOIL SOLARIZATION IN REDUCING TUBER RUSSET AND IMPROVING YIELD OF DIFFERENT POTATO CULTIVARS - Sharma, Jyotsana; Arora, R K. (Potato Journal, 2013)
Effect of soil solarization in reducing potato russet and improving yield in 15 varieties was studied. Russet incidence was reduced to about 40% in potato varieties except in Kufri Sindhuri, Kufri Sherpa, Kufri Lalima, Kufri Badshah and Kufri Jyoti which recorded reduction between 14.9 to 34.7% over unsolarized soil. Russet incidence in unsolarized soil, in different varieties varied from 4% in cv. Kufri Pukhraj to 99.7% in cv. Kufri Sherpa. Severity (DI) of russet was however, reduced to more than 40% in all varieties except cv. Kufri Sindhuri. Highest reduction of 80% in potato russet incidence and 88.3% in severity (DI) was recorded in cv. Kufri Ashoka. Solarization on an average recorded 26.8% increase in tuber yield. The increase in most of the varieties, was between 16-40 per cent.